(untitled) (Bangladesh Journal of Anatomy, 2016)
Context: Variations in the shape of the superior articular facets of the atlas vertebra between male and female is an interesting aspect of physical anthropometry. So that a standard data can be established for future studies in anatomy that can help forensic experts, spine surgeons, orthopedic surgeons and radiologists to adopt appropriate plans for diagnosis & treatment. Materials and methods: The study material consists of 152 (one hundred and fifty two) human dry ossified atlas vertebrae of unknown sex. The study samples were divided into male and female groups using the “discriminant function analysis technique” and the shapes of superior articular facets of atlas vertebrae were identified by simple observation method. Results: In the male atlases, 45.7% kidney- shaped, 30.9% oval- shaped, 9.9% dumb-bell shaped and 13.6% figure of 8- shaped superior articular facets were found on right side and 40.7% oval- shaped, 35.8% kidney- shaped, 16.0% dumb-bell -shaped, 7.4% figure of 8- shaped superior articular facets were found on left side. In the female atlases 62% oval -shaped, 33.8% kidney - shaped, 2.8%, dumbbell- shaped and 1.4% figure of 8 -shaped superior articular facets were found on right side and 63.4% oval, 31% kidney shaped, 4.2% dumb-bell shaped, 1.4% figure of 8- shaped superior articular facets were found on left side. Bangladesh Journal of Anatomy January 2016, Vol. 14, No. 1, pp. 9-12